2007
DOI: 10.1002/ejoc.200600912
|View full text |Cite
|
Sign up to set email alerts
|

Archazolid‐7‐O‐β‐D‐glucopyranoside – Isolation, Structural Elucidation and Solution Conformation of a Novel V‐ATPase Inhibitor from the Myxobacterium Cystobacter violaceus

Abstract: The novel polyketide macrolide archazolid-7-O-β-D-glucopyranoside (3) has been isolated from the myxobacterium Cystobacter violaceus and the structure of this first archazolidglycoside has been determined by spectroscopic and degradative methods. A synthesis of simplified 7-O analogues, based on regioselective derivatisation of archazolid A, was elaborated. These structurally novel archazolids of natural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…In the course of previous studies 27 the myxobacterium Cystobacter violaceus strain Cb vi105 22 has been identified as an efficient source for structurally novel archazolid derivatives, while Archangium gephyra strain Ar 3548 16 was a more productive source for archazolids A (1) and B (2). In order to study minor natural archazolid derivatives, each of these organisms was cultivated in 350 L bioreactors with 300 L of medium in the presence of Amberlite XAD-16 (1%) for adsorption.…”
Section: ' Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of previous studies 27 the myxobacterium Cystobacter violaceus strain Cb vi105 22 has been identified as an efficient source for structurally novel archazolid derivatives, while Archangium gephyra strain Ar 3548 16 was a more productive source for archazolids A (1) and B (2). In order to study minor natural archazolid derivatives, each of these organisms was cultivated in 350 L bioreactors with 300 L of medium in the presence of Amberlite XAD-16 (1%) for adsorption.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…19 Very recently, the binding site in this subunit has been analyzed in more detail by cross-linking experiments of an archazolid A derivative in combination with site-directed mutagenesis studies of the protein, demonstrating that archazolid A (1) binds to the equatorial region of the c-ring. 20 While the archazolids were originally isolated from Archangium gephyra, more recent reports have indicated that the myxobacterium Cystobacter violaceus produces a greater diversity of archazolids, and two other derivatives, archazolid C (3) 21 and archazolid D (4), with glucosides at C-7 (3 and 4) and an additional hydroxyl group (4), 22 have been isolated from this myxobacterium. While the archazolids were originally reported as planar structures, their absolute and relative stereochemistry was determined in 2006 by high-field NMR studies in combination with ABSTRACT: Two structurally novel analogues of the macrolides archazolids A and B, archazolid A-15-O-β-D-glucopyranoside (archazolid E, 5) and iso-archazolid B (archazolid F, 6), were isolated from the myxobacterium Cystobacter violaceus and Archangium gephyra, respectively.…”
mentioning
confidence: 99%
“…6B). In contrast, preincubation with apicularen A, a member of the benzolactone enamides family of V-ATPase inhibitors, which is predicted to have a binding site totally different from archazolid and the plecomacrolides (12,19,32), did not impede the binding of archazolid A as indicated by a clear prevention of NCD-4 labeling (Fig. 6A, lane 9).…”
Section: Labeling Of the V-atpase With A Radioactive Analog Of Archazmentioning
confidence: 93%
“…The most-potent representatives, archazolid A (1) and B (7) (Scheme 1), only differ in the methylation pattern at C-2; likewise reported glucosides 21,22 are less active by a factor of around 1000.…”
Section: Stereochemical Determinationmentioning
confidence: 97%